The effect of organic fertilizer and its extract and chemical fertilizer in some Vegetative and anatomical characteristics for three rootstock of citrus(Citrus spp.) - Al-taee, Zainab Turky; AL - Abbasi, Ghaleb B (Journal of Kerbala for Agricultural Sciences, 2018)
The experiment was carried out in the certified nursery for producing citrus seedlings which blowing to Ministry of Agriculture / Directorate General of Horticulture and Forests in the holy province of Karbala / Alhndia town during two growing seasons (2016-2017( and (2017-2018) Speed up the growth of rootstock of citrus (Citrus spp.) under the effect of fermented organic fertilizer and its extract and neutral chemical fertilizer. The experiment was conducted using Randomized complete block design with three factors: the first factor the citrus rootstock (Sour orange , swingle citrumelo and Volkamer lemon), the second factor fertilization with three rates (levels( of organic fertilizer (0, 5, 10, 15%) of soil weight and the third factor spraying with organic extract and chemical fertilizer (N-P-K ) (20- 20 - 20) at the same concentration (0.5%) in addition to control level to become three levels of the third factor. Results showed that there was a significant different between citrus rootstocks, where Sour orange was superior in diameter of stem character 2.32 and3.41 ml (in the first and second seasons), number of branches and anatomical character0.21 ml (in the second season only) whereas Swingle citrumelo rootstock was superior in the high of seedling71 and 90 cm (in the first and second seasons) and Volkamer lemon rootstock in number of leaves 50 and 102 leave.plant-1 and dry weight of vegetative growth 10.20and 33.78 g (in the first and second seasons) and fresh weight of vegetative growth 30.60 g (in the second season only). Also, the organic fertilizer and spraying with chemical fertilizer at level of 15% was superior compared with control treatment in all studied characteristics.